2022
DOI: 10.1161/jaha.121.022175
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alcohol Use Diagnostic Codes in Pregnancy and Offspring Conotruncal and Endocardial Cushion Heart Defects

Abstract: Background The pathogenesis of congenital heart disease (CHD) remains largely unknown, with only a small percentage explained solely by genetic causes. Modifiable environmental risk factors, such as alcohol, are suggested to play an important role in CHD pathogenesis. We sought to evaluate the association between prenatal alcohol exposure and CHD to gain insight into which components of cardiac development may be most vulnerable to the teratogenic effects of alcohol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The aortic narrowing in PHACES is specific to the aortic isthmus [14]. There is no increase in the frequency of aortic coarctation in infants born to mothers with the use of prenatal alcohol [15].…”
Section: Vascular Lesions In Wsmentioning
confidence: 92%
“…The aortic narrowing in PHACES is specific to the aortic isthmus [14]. There is no increase in the frequency of aortic coarctation in infants born to mothers with the use of prenatal alcohol [15].…”
Section: Vascular Lesions In Wsmentioning
confidence: 92%
“…Pregnancies complicated by fetal CHD often have maternal comorbidities that can provide clues for the role of the placenta in fetal CHD. Specifically, studies have shown an increased incidence of fetal CHD in pregnancies complicated by DM, 61–64 pre‐eclampsia, 65–68 uncontrolled hypertension, 69,70 alcohol or substance use, 71 smoking, 72 infections (REF), and other maternal diseases as well. Many of these morbidities also affect the placenta in characteristic ways, with some animal studies providing clues to the mechanistic link between these maternal morbidities and fetal CHD.…”
Section: Clinical Insights Into a Placental Origin Of Chdmentioning
confidence: 99%
“…Two studies evaluated conotruncal defects, of which one classified PAE in the periconceptional period [37,38]. In a case-control study in 2003, Carmichael [37] found slight increased odds of one or more drinks per week (OR 1.6, 95% CI 0.8, 3.0) among mothers of children born with conotruncal defects, but confidence intervals were very wide and overlapped the null.…”
Section: Conotruncal Heart Defectsmentioning
confidence: 99%
“…In a case-control study in 2003, Carmichael [37] found slight increased odds of one or more drinks per week (OR 1.6, 95% CI 0.8, 3.0) among mothers of children born with conotruncal defects, but confidence intervals were very wide and overlapped the null. Separately, a study utilizing California birth records found an association between conotruncal congenital heart disease and maternal alcohol-related ICD diagnosis during pregnancy (RR 1.6, 95% CI 1.2, 1.8) [38].…”
Section: Conotruncal Heart Defectsmentioning
confidence: 99%